Defending slavery proslavery thought in the Old South : A brief history with documents - Finkelman, Paul (The Bedford series in history and culture, 2003)
Offering invaluable insights into how slavery shaped American history and continues to affect American society, Defending Slavery: Proslavery Thought in the Old South shares viewpoints from proslavery, Southern thinkers based on religion, politics and law, economics, history, philosophy, expediency, and science.